Jordan chains of elliptic partial differential operators and Dirichlet-to-Neumann maps - Behrndt, Jussi; ter Elst, A. F. M. (Journal of spectral theory, 2021)
Let Ω \subset \mathbb{R}^d be a bounded open set with Lipschitz boundary Γ . It will be shown that the Jordan chains of m-sectorial second-order elliptic partial differential operators with measurable coefficients and (local or non-local) Robin boundary conditions in L_2(Ω) can be characterized with the help of Jordan chains of the Dirichlet-to-Neumann map and the boundary operator from H^{1/2}(Γ) into H^{-1/2}(Γ) . This result extends the Birman–Schwinger principle in the framework of elliptic operators for the characterization of eigenvalues, eigenfunctions and geometric eigenspaces to the complete set of all generalized eigenfunctions and algebraic eigenspaces.